THE ROLE OF VILLAGE-OWNED ENTERPRISES (BUMDes) TO RURAL DEVELOPMENT: A COMPARATIVE INSTITUTIONAL ANALYSIS - I Gede Agus Ariutama; Acwin Hendra Saputra; Renny Sukmono (Universitas Cenderawasih, 2018)
Government intervention for village development is carried out with various policies. The establishment of BUMDes is one of the government's efforts to accelerate rural development, advance the local economy, and develop the village partnerships and/or third party’s partnerships. This study exploits comparative institutional analysis framework to examine further how institutional aspects can affect the application of BUMDes in the rural development. The institutional aspects of BUMDes utilization for rural development is worth emphasizing since it will be employed as a foundation between the actors in a specific social area (structure) in its various forms such as rules, norms, or a certain routine, and the institution as a form of authority for the social behavior of the village organization. Furthermore, the successful implementation of BUMDes in the rural development is also affected by how stakeholder system can manage the institutional aspects. The result of this study, from the standpoint of comparative institutional analysis, underlines: (1) the limited authority of the Ministry of Villages, Underdeveloped Regions and Transmigration for rural development suggests that this Ministry must establish a specific institutional arrangement with the Ministry of Internal Affairs and Ministry of Cooperatives and Small and Medium Enterprises as well as banking institutions; (2) The village government has not fully taken advantage of the flexibility of its institutional arrangement to use BUMDes as a source of rural development; and (3) there is considerable scope to increase the role of BUMDes. This paper will propose some practical advices while considering the existing institutional arrangement.